2019
DOI: 10.31031/nacs.2019.03.000560
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of Epstein-Barr Virus and Human Cytomegalovirus Antigen Expression in Breast Cancer in Khartoum State, Sudan 2018

Abstract: Background: Breast cancer is a leading cause of death among women worldwide. The association between Epstein-Barr Virus (EBV) and Human Cytomegalovirus (HCMV) and breast cancer risk still remains controversial making it difficult to determine whether either, both or neither virus is causally associated with breast cancer. The aim of this study was to detect EBV and the expression of the Immediate Early Antigen (IE) of HCMV in breast cancer in Sudanese women.Method: 60 Formalin-fixed and paraffin-embedded tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Mohamed (22). In contrast, several studies found no association between HCMV infection and breast cancer (10,(23)(24)(25), or the CMV genome was identified only in 3% of healthy breast tissue samples using quantitative PCR (qPCR) (21).…”
Section: Antibodies In Postive Samples For CMV Genomementioning
confidence: 99%
“…Mohamed (22). In contrast, several studies found no association between HCMV infection and breast cancer (10,(23)(24)(25), or the CMV genome was identified only in 3% of healthy breast tissue samples using quantitative PCR (qPCR) (21).…”
Section: Antibodies In Postive Samples For CMV Genomementioning
confidence: 99%